Pemetaan dan Analisis Tren Penyakit Infeksi Menular Seksual di Kota Surabaya - Prilly Risni; Hari Basuki Notobroto (Universitas Airlangga, 2017)
Sexual Transmitted Disease (STD) was the entrance disease to the HIV/AIDS. The incidence of sexual transmitted disease that can not be known definitely makes this important. This study used mapping and trends to analyze the incidene of sexual transmitted disease that occur in Surabaya city and every sub-districts. This research was an observational research with analytic method. The data that used in this study was secondary data taken from district of health of Surabaya city in 2012–2016. Data were analyzed using linear regression. The results of linear regression showed that overall trend occured in Surabaya city and every sub-district was decreased. This study concludes that the trends of incedence of sexual transmitted disease during 2012–2016 mostly has negative results so it shows decreased incidence rate in every years.